Ahoy! - Blackall, Sophie (Anne Schwartz Books, 2024)
Join a child captain and parent first mate as they embark on a wild high seas adventure -- all without leaving the living room! This imaginative romp of a picture book is filled with glorious illustrations from a beloved Caldecott Medalist and New York Times bestselling creator.